Identification of the anisotropic behavior of the laser welded Interstitial Free steel HC260Y subjected to uniaxial tensile tests (Fracture and Structural Integrity, 2022)
The main purpose of this paper is to study the anisotropicbehavior of laser welded interstitial free steel HC 260Y when it is subjectedto monotonic tensile tests. The specimens were cut in different orientationsaccording to the rolling direction, annealed and finally assembled by laserwelding. The plastic behavior was modelled using an identification strategybased on a behavior law taking into account the anisotropy of this material, ahardening law describing the evolution of the hardening curves and anevolution law. The proposed identification strategy allowed for a goodvalidation of the model. The model was afterwards used to predict thebehavior of the welded material when it is subjected to various solicitations.Finally, the fracture surfaces of the specimens were examined using thescanning electron microscope (SEM) to determine the failure characteristicsunder the tensile loading.
Keywords: Interstitial Free steel; Laser welding; off-axis tensile tests; anisotropy; identification strategy; SEM